Should attractive males sneak: the trade-off between current and future offspring. - Ulrika Candolin (Public Library of Science (PLoS), 2013)
Alternative reproductive tactics are predicted to be adopted by less competitive males when competition for fertilization is intense. Yet, in some species, competitively superior males use an alternative tactic alongside the conventional tactic. This can jeopardize their success through the conventional tactic, but surprisingly little attention has been paid to this cost. We investigated 1) the degree to which competitive males sneak fertilize eggs in the polygamous threespine stickleback, Gasterosteus aculeatus, and 2) if males balance the cost of sneaking against its benefit. We found competitive males that succeeded in establishing a territory and in attracting spawning females to perform most sneak fertilizations. However, when we reduced the benefit of sneak attempts, by reducing visibility and the success rate of sneak attempts, males sneaked less. When we increased the cost of sneak attempts, by increasing the perceived value of current offspring (by mating males to preferred females rather than unpreferred females or no females), the interest of males in sneak opportunities decreased. Intriguingly, larger males, who presumably had a higher probability of future reproduction, were more willing to risk their current offspring for sneak opportunities. These findings suggest that competitive males that are attractive to females carefully balance costs against benefits in their sneaking decisions. More broadly, our results imply that changes in the environment can influence the cost-benefit ratio of sneaking and alter the distribution of fertilizations in a population. We end with discussing the implications that alterations in sneaking behavior could have for the operation of sexual selection in changing environments.